PENGARUH LEVERAGE, LIKUIDITAS, PERTUMBUHAN, UMUR PERUSAHAAN, DAN UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN - Michella, Aurellia; Wijaya, Henryanto (Jurnal Paradigma Akuntansi, 2024)
The purpose of this study is to determine the effect of leverage, liquidity, growth, firm age, and firm size on firm performance in family manufacturing companies listed on Indonesia Stock Exchange (IDX) during 2018-2020 period. This study used 48 data from family manufacturing companies which has been selected with purposive sampling method with the total of 144 data from the 2018-2020 period. Data is processed using computer-based program Eviews version 12. Multiple linear regression analysis is used in this study. The results of this study indicate that leverage has a positive and significant effect on firm performance. Liquidity has a positive and not significant effect on firm performance. Growth has a positive and significant effect on firm performance. Firm age has a positive and not significant effect on firm performance. Firm size has a positive and not significant effect on firm performance. The implication in this study is that companies need to observe the debt level that they have, good utilization of assets and expenses will increase the profit earned by the company and this will improve the company’s performance.